The Environmental Management and Recreational Facilities Usage: A Study Of Kainji Lake National Park - Kolawole, G.T,; Omotayo O.L.,; Adedeji E.O.,; Chikezie, J.,; Deji Joshua,; Onihunwa, John Ojo,; Elizabeth Abidemi Akintade, (Technium Social Sciences Journal, 2020)
Assessment of Environmental and Recreation Facility Maintenance was carried out in Kainji Lake National Park. Questionnaire method of data collection was employed to collect the data needed. Purposive and simple random techniques were adopted to sample respondents in the study area. One hundred questionnaires were designed and administered. The data collected were analyzed through simple percentage and presented in table and charts. However, the results showed that recreation facilities are 99% present, while swimming pool is 65% functional. The study showed that visitors came there three times in a week indicating 44% of the respondents while on maintenance of the park environment and the facilities indicated 94% and 88% of the respondents respectively. The study further recommended the followings facilities basketball pitch. Hockey game, volley ball and well-constructed swimming pool.